2005
DOI: 10.1213/01.ane.0000181005.50958.1e
|View full text |Cite
|
Sign up to set email alerts
|

Administration of Local Anesthetic Through the Epidural Needle Before Catheter Insertion Improves the Quality of Anesthesia and Reduces Catheter-Related Complications

Abstract: Epidural catheter placement offers flexibility in block management. However, during epidural catheter insertion, complications such as paresthesia and venous and subarachnoid cannulation may occur, and suboptimal catheter placement can affect the quality of anesthesia. We performed this prospective, randomized, double-blind study to assess the effect of a single-injection dose of local anesthetic (20 mL of 2% lidocaine) through the epidural needle as a priming solution into the epidural space before catheter i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
26
2
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 17 publications
1
26
2
1
Order By: Relevance
“…Saline, however, dilutes the local anesthetic injected; in this study, we therefore administered a single-injection dose of local anesthetic (20mL) as a priming solution as done by Cesur et al (5) This study also demonstrated improved surgical conditions with the administration of a single-injection dose through an epidural needle before epidural catheter placement. (5) However, Rolbin et al (8) and Scott and Beilby (9) reported no advantage in injecting fluid into the epidural space before catheter insertion, but they administered much smaller volumes of fluid (3 and 5mL, respectively) for priming. However, Paresthesia during epidural catheter insertion has been reported in up to 60% of parturients, (10) and the frequency of venous and subarachnoid cannulation has been studied and there complications were reported.…”
Section: Discussionmentioning
confidence: 82%
See 3 more Smart Citations
“…Saline, however, dilutes the local anesthetic injected; in this study, we therefore administered a single-injection dose of local anesthetic (20mL) as a priming solution as done by Cesur et al (5) This study also demonstrated improved surgical conditions with the administration of a single-injection dose through an epidural needle before epidural catheter placement. (5) However, Rolbin et al (8) and Scott and Beilby (9) reported no advantage in injecting fluid into the epidural space before catheter insertion, but they administered much smaller volumes of fluid (3 and 5mL, respectively) for priming. However, Paresthesia during epidural catheter insertion has been reported in up to 60% of parturients, (10) and the frequency of venous and subarachnoid cannulation has been studied and there complications were reported.…”
Section: Discussionmentioning
confidence: 82%
“…(5) Gadalla et al (6) Mannion et al, (7) all noted a significant reduction in the incidence of extradural vein cannulation by routinely injecting 10 mL of saline priming fluid into the epidural space before catheter insertion. Saline, however, dilutes the local anesthetic injected; in this study, we therefore administered a single-injection dose of local anesthetic (20mL) as a priming solution as done by Cesur et al (5) This study also demonstrated improved surgical conditions with the administration of a single-injection dose through an epidural needle before epidural catheter placement. (5) However, Rolbin et al (8) and Scott and Beilby (9) reported no advantage in injecting fluid into the epidural space before catheter insertion, but they administered much smaller volumes of fluid (3 and 5mL, respectively) for priming.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…4 An effective method for the management of postoperative pain after lower abdominal or lower extremity surgery is using epidural analgesia with local anesthetics, but it is a highly techniquedependent and invasive procedure. 5 Adhesion, on the other hand, is a band of scar tissue that binds two parts of tissues or organs together. 6 Adhesions form when the body's repair mechanisms respond to any tissue disturbances, such as surgery, infection, trauma, or radiation.…”
Section: Introductionmentioning
confidence: 99%